The Stereochemistry of Pyrrolidine Ring Biosynthesis in Tobacco - Wigle, Ian D. (My University, 1983)
In four separate experiments, DL-[5-3H]/DL-[5-14C]ornithine, L-[5-3H]/DL- [5- 14C]ornithine, D-[5-3H]/DL- [5- 14C]ornithine and L-[2-3H]/L-[5- 14c]ornithine were administered to intact tobacco plants (Nicotiana tabacum). Nicotine, ornithine and proline were isolated in each of these experiments. In another experiment, R-[1-2H][l ,4-14C] putrescine was administered to intact tobacco plants and nicotine was isolated. The results of these experiments are consistent with the accepted mode of biosynthesis of nicotine from ornithine via putrescine (1,4-diaminobutane), N-methylputrescine, N-methyl-4-aminobutanal and N- methyl-1-pyrrolinium ion. The 3H:14c ratios of nicotine, the distribution of tritium within nicotine as established by chemical degradation and the distribution of deuterium within nicotine as established by 2H NMR are interpreted as showing that L-ornithine is the preferred enantiomer for nicotine biosynthesis, that the decarboxylation of L-ornithine to yield putrescine proceeds with retention of configuration at the reaction site, and that the oxidation of N-methylputrescine to N-methyl-4-aminobutanal proceeds with loss of the 4(S)hydrogen.
Contrary to earlier reports, ornithine isolated in the 3H, 14C experiments had a changed 3:14c ratio from the ornithine which was fed. These results are interpreted as showing that L-ornithine is metabolised more rapidly than is D-ornithine in the tobacco plant.
In all 3H, 14c experiments, proline was found to contain at least a small amount of tritium. In particular, when L-[2- 3H]/L-[5-14C] ornithine served as substrate, proline was found to contain 40 + 1% of the tritium, relative to 14C, that had been present in the feeding material. This result is interpreted as showing that, contrary to earlier reports, L-ornithine can be converted into proline via either a-keto-s-aminovaleric acid or glutamic semialdehyde. Together with the 3H: 14C ratios of proline in the other experiments, the results of this work are interpreted as showing that, when DL-ornithine serves as the substrate for proline biosynthesis in tobacco, 88 + 1% of the proline arises from D-ornithine via a-oxidation, 7 + 1% of the proline comes from L-ornithine via a-oxidation and 5 + 1% of the proline is produced from L-ornithine via s-oxidation.
Keywords: pyrrolidine ring biosynthesis; Tobacco; stereochemistry; proline biosynthesis; ornithine